Comparative Analysis of the Combined Effects of Different Water and Phosphate Levels on Growth and Biological Nitrogen Fixation of Nine Cowpea Varieties - Jemo, Martin; Sulieman, Saad; Bekkaoui, Faouzi; Olomide, Oluwatosin A. K.; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Alqarawi, Abdulaziz A.; Tran, Lam-Son Phan (Frontiers in Plant Science, 2017)
Water deficit and phosphate (Pi) deficiency adversely affect growth and biological nitrogen fixation (BNF) of legume crops. In this study, we examined the impact of interaction between soil water conditions and available soil-Pi levels on growth, nodule development and BNF potential of nine cowpea varieties grown on Dry Savanna soils. In our experimental design, soils with different available soil-Pi levels, i.e. low, moderate and high soil-Pi levels, collected from various farming fields were used to grow nine cowpea varieties under well-watered and water-deficit conditions. Significant and severe water deficit-damaging effects on BNF, nodulation, growth, levels of plant-nitrogen (N) and -phosphorus (P), as well as shoot relative water content and chlorophyll content of cowpea plants were observed. Under well-watered and high available soil-Pi conditions, cowpea varieties IT07K-304-9 and Dan’Ila exhibited significantly higher BNF potential and dry biomass, as well as plant-N and -P contents compared with other tested ones. Significant genotypic variations among the cowpeas were recorded under low available soil-Pi and water-deficit conditions in terms of the BNF potential. Principal component (PC) analysis revealed that varieties IT04K-339-1, IT07K-188-49, IT07K-304-9 and IT04K-405-5 were associated with PC1, which was better explained by performance for nodulation, plant biomass, plant-N, plant-P and BNF potential under the combined stress of water deficit and Pi deficiency, thereby offering prospects for development of varieties with high growth and BNF traits that are adaptive to such stress conditions in the region. On another hand, variety Dan’Ila was significantly related to PC2 that was highly explained by the plant shoot/root ratio and chlorophyll content, suggesting the existence of physiological and morphological adjustments to cope with water deficit and Pi deficiency for this particular variety. Additionally, increases in soil-Pi availability led to significant reductions of water-deficit damage on dry biomass, plant-N and -P contents, and BNF potential of cowpea varieties. This finding suggests that integrated nutrient management strategies that allow farmers to access to Pi-based fertilizers may help reduce the damage of adverse water deficit and Pi deficiency caused to cowpea crop in the regions, where soils are predominantly Pi-deficient and drought-prone.